2019
DOI: 10.1002/adfm.201906586
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Branched Lamination of Hierarchical Patronite Nanoarchitectures on Carbon Fiber Cloth as Novel Electrode for Ionic Liquid Electrolyte‐Based High Energy Density Supercapacitors

Abstract: The developments of rationally designed binder-free metal chalcogenides decorated flexible electrodes are of paramount importance for advanced energy storage devices. Herein, binder-free patronite (VS 4 ) flower-like nanostructures are facilely fabricated on a carbon cloth (CC) using a facile hydrothermal method for high-performance supercapacitors. The growth density and morphology of VS 4 nanostructures on CC are also controlled by varying the concentrations of vanadium and sulfur sources along with the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…Benefiting from the high areal capacitance performance and extended operating voltage window, the solid‐state asymmetric device can deliver a maximum areal energy density up to 277.3 μWh cm −2 at a power density of 624 μW cm −2 (Figure 5e). The obtained areal energy density outperforms those of ever‐reported MXene‐based symmetric and asymmetric supercapacitors including RuO 2 //Ti 3 C 2 yarn (1.5 V; 168 μWh cm −2 ), [ 47 ] PANI//Ti 3 C 2 T x (1.4 V; 159 μWh cm −2 ), [ 44 ] Ti 3 C 2 aerogel//CNF (1.3 V; 120 μWh cm −2 ), [ 48 ] RuO 2 //Ti 3 C 2 sandwich (1.5 V; 48 μWh cm −2 ), [ 34 ] 1TMoS 2 /Ti 3 C 2 (0.6 V; 17.4 μWh cm −2 ), [ 49 ] MXene/MPEs (0.6 V; 20.4 μWh cm −2 ) [ 42 ] and these in Table S1, Supporting Information, which is also remarkably outstanding in many textile‐based supercapacitors such as activated graphene fiber fabric (0.8 V; 23.5 μWh cm −2 ), [ 50 ] VS4‐CC@VS‐3 (2.0 V; 74.4 μWh cm −2 ), [ 51 ] activated carbon cloth (1.0 V; 77 μWh cm −2 ), [ 15 ] CF/MoO 3 //CF/MnO 2 (2.0 V; 2.7 μWh cm −2 ), [ 52 ] Co 9 S 8 @PPy@NiCo‐LDH‐NTAs//AC (1.6 V, 132 μWh cm −2 ), [ 53 ] Cu(OH) 2 /CPCC//AC/CC (1.2 V, 49 μWh cm −2 ) [ 54 ] and these in Table S2, Supporting Information. Even at the highest power density of 26 480 μW cm −2 , the solid‐state asymmetric device can achieve a high areal energy density of 117.7 μWh cm −2 , indicative of outstanding rate capability.…”
Section: Resultsmentioning
confidence: 99%
“…Benefiting from the high areal capacitance performance and extended operating voltage window, the solid‐state asymmetric device can deliver a maximum areal energy density up to 277.3 μWh cm −2 at a power density of 624 μW cm −2 (Figure 5e). The obtained areal energy density outperforms those of ever‐reported MXene‐based symmetric and asymmetric supercapacitors including RuO 2 //Ti 3 C 2 yarn (1.5 V; 168 μWh cm −2 ), [ 47 ] PANI//Ti 3 C 2 T x (1.4 V; 159 μWh cm −2 ), [ 44 ] Ti 3 C 2 aerogel//CNF (1.3 V; 120 μWh cm −2 ), [ 48 ] RuO 2 //Ti 3 C 2 sandwich (1.5 V; 48 μWh cm −2 ), [ 34 ] 1TMoS 2 /Ti 3 C 2 (0.6 V; 17.4 μWh cm −2 ), [ 49 ] MXene/MPEs (0.6 V; 20.4 μWh cm −2 ) [ 42 ] and these in Table S1, Supporting Information, which is also remarkably outstanding in many textile‐based supercapacitors such as activated graphene fiber fabric (0.8 V; 23.5 μWh cm −2 ), [ 50 ] VS4‐CC@VS‐3 (2.0 V; 74.4 μWh cm −2 ), [ 51 ] activated carbon cloth (1.0 V; 77 μWh cm −2 ), [ 15 ] CF/MoO 3 //CF/MnO 2 (2.0 V; 2.7 μWh cm −2 ), [ 52 ] Co 9 S 8 @PPy@NiCo‐LDH‐NTAs//AC (1.6 V, 132 μWh cm −2 ), [ 53 ] Cu(OH) 2 /CPCC//AC/CC (1.2 V, 49 μWh cm −2 ) [ 54 ] and these in Table S2, Supporting Information. Even at the highest power density of 26 480 μW cm −2 , the solid‐state asymmetric device can achieve a high areal energy density of 117.7 μWh cm −2 , indicative of outstanding rate capability.…”
Section: Resultsmentioning
confidence: 99%
“…The energy and power relationship was depicted as a Ragone plot and compared with previously reported high‐performance supercapacitors (Figure 4f). [ 39–46 ] The MEC‐based Mg ion supercapacitors offered at least double the specific energy density and over four times the specific power density offered by previously reported Mg ion supercapacitors. In addition, this multivalent ion supercapacitor exceeded the energy and power capabilities of all other alkali ion‐based supercapacitors reviewed in the comparison.…”
Section: Resultsmentioning
confidence: 97%
“…These properties, along with high intrinsic ionic conductivity, are highly desirable as solvents and electrolytes for SCs. Earlier results suggested that the capacitance retention and operational safety at high temperatures is much better for SCs with ILs as electrolytes than those using non-aqueous electrolytes [11,25,75,[178][179][180][181][182][183][184][185][186][187][188]. It is also observed that SCs fabricated using ILs can be operated at high cell voltage, which helps the improvement of energy density of SCs to the extent of secondary batteries [180][181][182][183][184][185][186][187][188][189][190][191][192][193].…”
Section: Pristine Ionic Liquids As Electrolytesmentioning
confidence: 99%